War disasters and their effects on urban structure, historic buildings, local people and architectural heritage - Al-Kawafi, Hussain Saleh Mohammed (Journal of engineering sciences and information technology, 2024)
Many urban areas are located under the weight of disasters, whether natural or industrial, and in light of the increasing complexity in urban areas, the diversity of economic, social and political components and technological and cognitive development, the effects of disasters and wars have increased from before, as disasters greatly affect all joints of life and cause waste of property and lives, displacement of the population and disruption of economic life, and these effects multiply if they are not dealt with with sound curricula and scientific strategies. The research aims to identify the experiences of some countries, their strategies and effective programs in reconstruction after exposure to disasters and wars within urban areas, using the descriptive and analytical approach and disaster management in urban areas within the experiences of effective countries in overcoming the effects caused by disasters on the urban structure in its various components, assuming that identifying the experiences of some countries in disaster management contribute to identifying successful practices and providing effective urban management for areas prone to wars and disasters and developing appropriate strategies for that, The main problem of the existence of the direct and indirect effects of wars and disasters in the city of Benghazi with the absence of an appropriate approach and strategies to deal with these damages has been identified to a set of relevant conclusions and recommendations for the purpose of research.
Keywords: disasters; wars; strategic planning; reconstruction; urban planning